The effects of noise on speech intelligibility in telephone communication - Tan, K.L.; Tang, S.H.; Ong, P.P.; Sy, H.K. (Canadian Acoustics, 1984)
Presents the subjective ratings of speech intelligibility in broadband ambient noise as a function of signal level for telephone communication. The appraisals were evaluated for English messages in an acoustic studio by Asian subjects conversant in the language. To present the necessary signal levels for satisfactory intelligibility under different levels of steady and fluctuating noise fields, two speech interference criteria expressed separately in terms of the preferred speech interference level (PSIL) and L50 were proposed